Ministers of parliament and information and communication technologies as a means of horizontal and vertical communication in Western Europe - Cardoso, G.; Cunha, C.; Nascimento, S. (Information Polity, 2004)
The analysis in this article focuses on the vertical and horizontal communication patterns of MPs, drawing on examples from a comparative survey done in seven European countries. The results show that the MPs in these countries can still be said to be in an initial phase of exploiting the full range of these new technologies to support their parliamentary and partisan activity, and that traditional media such as television, radio and newspapers are still the favoured means for political communication. In so far as ICT is used, MPs primarily use these means for internal communication within the party or within parliament, and not very much for external communication with constituents, journalists, lobbyists, etc. Analysing the use of homepages and political campaign via ICT, both of these means are seen to be largely dependent on the political party of the MP, and the party's electoral strategies, limiting individual initiatives by MPs. Also, a certain disinterest in a more extensive use, of ICT on the part of the MPs was found. There seem to be a number of reasons for this disinterest, among these the argument that there is still a considerable digital divide especially in the Southern European countries. However, as computer and Internet diffusion continues to increase rapidly, this argument becomes increasingly invalid.